Luminescence and Internal Quantum Efficiency of Deep UV Light Emitting Diodes - Romer, Friedhard; Witzigmann, Bernd (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2020)
Deep ultraviolet (DUV) light emitting diodes (LED) made of Aluminium Gallium Nitride (AlGaN) are increasingly considered as light sources for medical as well as material processing applications. Recent research on AlGaN DUV LEDs focuses on the enhancement of the efficiency. The efficiency of AlGaN LEDs is limited by a low hole injection efficiency and TM-polarized emission requiring a careful design. In this context we are demonstrating the physics based modelling of AlGaN DUV LEDs by means of a self consistent simulation approach. The simulation model is validated and calibrated comparing experiment and simulation. We demonstrate that electron leakage presents a major contribution to the internal loss and analyse the impact of the active region design.
CRIS-Team Scopus Importer:2021-06-11